Rare bird documentation form for Greater Scaup at Little Clear Lake in 1985 - Carlson, Judithet al (1985)
Rare bird documentation form for ten to fifteen Greater Scaups at Little Clear Lake in Pocahontas County, IA on April 6, 1985. Epson - sheet feed